Measurement of the fluorescence lifetime of GFP in high refractive index levitated droplets using FLIM. Issue 26 (23rd June 2020) - Davidson, N. M.; Gallimore, P. J.; Bateman, B.; Ward, A. D.; Botchway, S. W.; Kalberer, M.; Kuimova, M. K.; Pope, F. D.
Abstract : This work demonstrates that green fluorescent protein (GFP) can be used as a probe to study aerosols and droplets; in particular GFP, can be used as a probe of refractive index. Abstract : Green fluorescent protein (GFP) is a widely used fluorescent probe in the life sciences and biosciences due to its high quantum yield and extinction coefficient, and its ability to bind to biological systems of interest. This study measures the fluorescence lifetime of GFP in sucrose/water solutions of known molarity in order to determine the refractive index dependent lifetime of GFP. A range of refractive indices from 1.43–1.53 were probed by levitating micron sized droplets composed of water/sucrose/GFP in an optical trap under well-constrained conditions of relative humidity. This setup allows for the first reported measurements of the fluorescence lifetime of GFP at refractive indices greater than 1.46. The results obtained at refractive indices less than 1.46 show good agreement with previous studies. Further experiments that trapped droplets of deionised water containing GFP allowed the hygroscopic properties of GFP to be measured. GFP is found to be mildly hygroscopic by mass, but the high ratio of molecular masses of GFP to water ( ca. 1500 : 1) signifies that water uptake is large on a per-mole basis. Hygroscopic properties are verified using brightfield microscope imaging, of GFP droplets at low and high relative humidity, by measuring the humidity dependent droplet size. In addition, this experiment allowed the refractive index of pure GFP to be estimated for the first time (1.72 ± 0.07). This work provides reference data for future experiments involving GFP, especially for those conducted in high refractive index media. The work also demonstrates that GFP can be used as a probe for aerosol studies, which require determination of the refractive index of the aerosol of any shape.